Hots Ability Profile (High Order Thinking Skill) Evaluation Level of Biology Material for High School/MA Students in Banten Province - Mila Ermila Hendriyani; Dwi Ratnasari; Ika Rifqiawati; Nurlailah Sari; Mahrawi Mahrawi (PT FORMOSA CENDEKIA GLOBAL, 2023)
This research aims to determine the HOTS (High Order Thinking Skill) ability profile at the evaluation level of biology material for high school/MA students throughout Banten Province. This research was conducted in 16 schools in Banten Province which were taken using a simple random sampling technique. The research subjects consisted of 320 students who worked on HOTS questions, then of the 320 students, 80 students were taken to work on an open questionnaire, and 8 teachers were interviewed regarding HOTS abilities at evaluation level (C5). The research results show that the HOTS level evaluation (C5) abilities of SMA/MA students in Banten Province are still very low with an average score of 18.10, which is in the very poor category. Students who have evaluation level HOTS abilities in the very poor category are 62%, 26% in the poor category, 10% in the sufficient category, 2% in the good category, and 0% of students who have evaluation level HOTS abilities in the very good category.